Effect of nanosilica treatment on mechanical properties of hybrid jute-high tenacity polyester/unsaturated polyester composites. Issue 5 (4th May 2023) - Ahmadi, Mohammad Saleh; Hasanzadeh, Mahdi; Dehestani, Parisa; Dastan, Tohid
ABSTRACT: In this study, the effect of nanosilica modification on mechanical properties of unsaturated polyester composites reinforced with pure jute and hybrid jute-high tenacity polyester (HTPET) fabrics was evaluated. The mechanical properties of the composites were investigated by the tensile, flexural, and impact tests. The effect of nanosilica modification on the fabric surface chemistry and morphology was studied using Fourier transform infrared (FTIR) spectroscopy and scanning electron microscopy (SEM). The results showed that nanosilica modification lead to improved adhesion of polyester fibers to the matrix with the surface roughing mechanism. However, in the case of jute fibers, due to the filling and smoothing of inherent roughness of this fiber, it reduces the adhesion. The largest increase in mechanical properties was also observed in flexural and impact properties for the hybrid sample with polyester fibers in its outer layers. GRAPHICAL ABSTRACT: uf0001